Feedback of the participants on assessment sessions conducted in faculty development training at National Center for Health Professions Education Nepal - Piryani, Rano Mal; Piryani, Suneel; Shahi, Mandira (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: It is essential for health professions educators to be cognizant and coached on what level, assessment is being conducted according to Blooms Taxonomy or Miller’s Pyramid and trained to conduct assessment. The objective of this study was to take feedback of the participants on sessions of assessment. Materials and Methods: Six-hours assessment sessions conducted in faculty development training organized by National Centre for Health Professionals Education, Tribhuvan University Institute of Medicine, Kathmandu Nepal in August 12-17, 2018. Principal author conducted three sessions (2 hours each)- 1) educational evaluation & assessment and fundamentals of assessment, 2) assessment of knowledge & understanding and 3) OSCE and OSPE in training. The methods utilized were tutorial, brainstorming and activity based small group work. Feedback was taken on semi-structured questionnaire. Descriptive analysis was done using SPSS. Results: Twenty-two participants selected from basic, clinical and dental sciences and nursing faculty of seven schools. The participants rated assessment sessions on scale of 1-10 (1= poor, 10= excellent) for usefulness (8.42 ± 1.53), content (8.08 ± 1.61), relevance of session & content (8.50 ± 1.53), facilitation (8.00 ± 1.56) and overall (8.42 ± 1.31). They gained confidence for developing blueprint for assessment (2.96±0.86), developing MCQs (3.67±0.76), developing SAQs (3.42±0.93), constructing OSCE/OSPE (2.92±0.97) and conducting OSCE/OSPE (2.92±0.77) rated at Likert scale1-5 after participating in training. Sufficient number of participants suggested to allocate more time for assessment sessions and increase time for group work. Conclusion: It is noticed that participants recognize and acknowledge the importance of assessment and their confidence level has increased for developing blueprint, MCQs, SAQs, OSCE/OSPE and conducting OSCE/OSPE examination.